Biochemical and agro-morphological traits-based mining for Malt Barley Germplasm - Khera, Shakti; Kumar, Prakash; Tripathi, Shashi Bhushan; Jacob, Sherry Racheal; Kumar, Dinesh; Singh, Charan; Bhardwaj, Rakesh; Ahlawat, Sudhir Pal; Rana, Jai Chand; Riar, Amritbir (Frontiers in Nutrition, 2025)
Barley serves as a crucial feed crop and is also utilized for baking, malting, and brewing purposes. In India, the consistent demand for malting-type barley has not been met due to the lack of suitable varieties. This study evaluated 136 barley germplasm accessions for diversity in biochemical and agro-morphological traits. The accessions were grown in Augmented Block Design and biochemical estimations were carried out using official and standard methods. The accessions exhibited substantial biochemical diversity with protein content (PC) ranging from 8.6 to 17.4%, starch content (SC) from 32.4 to 60.3%, amylose content (AC) from 13.3 to 19.3%, β-glucan content (βgC) from 1.31 to 6.06%, and total phenol content (TPC) from 8.6 to 17.4%. The agro-morphological traits also displayed considerable variation, with days to spike emergence (DSE) ranging from 74 to 124 days, days to physiological maturity (DPM) from 119 to 147 days, plant height (PH) from 82 to 165 cm, spike length (SL) from 5 to 11 cm, spikelet triplet groups (STG) per spike from 13 to 35, grain number per spike (GNS) from 15 to 71, hundred-grain weight (HGW) from 2 to 6.7 grams, and grain yield per meter row (GY) from 13.7 to 236.3 grams. Multivariate analyses, including the Mantel test, Pearson’s correlation, principal component analysis (PCA), and hierarchical cluster analysis (HCA), were conducted. No significant correlation was observed between biochemical and agro-morphological traits. However, significant positive correlations were found between SC and AC (r = 0.48) and βgC with PC (r = 0.2). Significant negative correlations were observed between SC and PC (r = −0.41) and AC with PC (r = −0.4). Highly significant positive correlations were observed between DSE and DPM (r = 0.55), GY and PH (r = 0.29), PH and DPM (r = 0.2), and HGW and SL (r = 0.25). The GWL was significantly positively correlated with βgC (r = 0.257) and significantly negatively correlated with TPC (r = −0.235). Apart from Grain Width to Length Ratio (GWL), no other agro-morphological trait was significantly correlated with any biochemical trait. Various accessions suitable for malting, human food, and cattle feed applications were identified.